1982
DOI: 10.2337/diab.31.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Induced Alterations in Insulin Binding and Insulin Action in Primary Cultures of Rat Hepatocytes

Abstract: We have recently proposed that "down regulation" of the insulin receptor may be one of the many biological responses of a cell to insulin. In an attempt to further explore this hypothesis we have studied insulin action, binding, and degradation in freshly isolated hepatocytes from rats rendered insulin resistant by the administration of dexamethasone, 1.0 mg/kg every other day, for 1 and 4 wk, and in dexa-methasone-treated (0.1 ,uM for 24 h) primary cultures of hepatocytes from normal rats. Dexamethasone treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…Conversely, insulin-stimulated de novo lipogenesis was unchanged relative to vehicle treatment (Fig. 2D), consistent with previous data in rat hepatocytes (11). Moreover, CHI-treated cells showed a non-significant trend toward increased rates of DNL in the basal and insulin-stimulated states relative to control cells.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Conversely, insulin-stimulated de novo lipogenesis was unchanged relative to vehicle treatment (Fig. 2D), consistent with previous data in rat hepatocytes (11). Moreover, CHI-treated cells showed a non-significant trend toward increased rates of DNL in the basal and insulin-stimulated states relative to control cells.…”
Section: Resultssupporting
confidence: 80%
“…Although previous studies investigating expression of lipogenic genes in primary hepatocytes suggested this possibility, these studies did not measure DNL directly (10,32,33,57). On the other hand, older studies that also provide evidence that DNL continues unabated in the face of CHI did not correlate these data with lipogenic gene expression or compare them to GP (8,11,16).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, it is likely that insulin sensitizes the insulin-resistant adipocytes. Whereas, it desensitizes the normal adipocytes and the evidence to support this contention is overwhelming in various animal cell models (17)(18)(19)(20)(21)(22)(23)(24). To test these hypotheses directly, we have developed a primary culture system for insulin-responsive human adipocytes from control and morbidly obese subjects with or without NIDDM.…”
Section: Introductionmentioning
confidence: 99%